Analyzing Search Interest Data for Political Figures in Andhra Pradesh (International Journal of Food and Nutritional Sciences, 2019)
This research report aims to analyze search interest data for prominent political figures inAndhra Pradesh from 2014 to 2021. The study focuses on the online search behavior ofresidents in Andhra Pradesh concerning key political personalities, including N. ChandrababuNaidu, YS Jagan Mohan Reddy, KA Paul, Jayaprakash Narayan, and Pawan Kalyan. Theresearch seeks to uncover patterns in online search interest, identify factors that drive interestfluctuations, and understand the significance of these findings in the political landscape ofAndhra Pradesh.